Analisis Determinan Financing to Deposit Ratio Pada Bank Umum Syariah di Indonesia Periode 2017-2022 - Eka Fauziah Rizky; Destian Arshad Darulmalshah Tamara; Fatmi Hadiani (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to determine the magnitude of the influence of the variables Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Return on Assets (ROA), Net Operating Margin (NOM), and Inflation on Financing to Deposit Ratio (FDR) at at Sharia Commercial Banks in Indonesia 2017-2022 period. The population used is Sharia Commercial Banks in Indonesia. The data used is secondary data derived from the annual report for the 2017-2022 period which is available on each BUS website. The research method used is quantitative research with panel data regression analysis. The result of this study conclude that DPK has a negative no significant effect on FDR, CAR has a significant positive effect on FDR, ROA has a negative no significant effect on FDR, NOM has a positive no significant effect on FDR, and Inflation has a negative no significant effect on FDR. Car has a dominant effect on FDR.